Pessoas que lembram: lazeres nas memórias e histórias de moradores de Serra Branca-PB (1940-1970) - Leite, Fabiolla Stella Maris de Lemos Furtado (2012)
The objective of this work is to present and analyse the engendred memories of the proportionated experiences by the leisure in Serra Branca city in Paraíba, such as the carnival and Nossa Senhora's da Conceição Celebrations, by cultural programs in the old cinema called Educational Cine, by Radio Castelo Branco, by soccer games of the local teams- Vasco da Gama and Flamengo. We understand memory as an important means of development, dissemination and reception of relations with the past allows us to establish links with the area of concentration this program graduate, namely History and Historical Culture, and more specifically, with the line of research Teaching of History and Historical Knowledge. The temporal cut - decades of 1940 to 1970 has been defined considering the complex relations between present and past, caracteristics of memory. The relevance of this work lies in fact that it seeks to contribute together with productions about local history, here delimited as history of cities, specifically in the Paraiba's case. Objectifying to apprehend the lived experiences for some locals from Serra Branca evaluating the importance of these experiences to elaboration of a local history designed by a cultural cut. Employing reflections about: history, memory, local history, cutural pratices, celebrations , leisure and experience, through of a varied theorical contribution , which enabled to transit between theory and analysis from the produced sources , in the case of these last, resorting to the methodology of oral history, performing interviews with residents from the cited Town.